Financial Intermediation Versus Stock Markets in a Dynamic Intertemporal Model - Riccardo Rovelli; Paolo Fulghieri; Sudipto Bhattacharya (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1997)
We consider the transitions among intragenerational and alternative intergenerational financing and liquidity risk-sharing mechanisms, in an Overlapping Generations model with endogenous levels of long-lived investments. The existence and characterization of a Self-Sustaining Mechanism, stable across generations, are established. The long-run equilibrium outcome, in a Proposal Game across generations, is shown to depend on the risk-aversion and propensity for early liquidity needs of the agents.
Keywords: 330